A study on knowledge sharing practices and innovation capability: A social capital perspective / Ahmad Vazehi Ashtiani - Ashtiani, Ahmad Vazehi (2014)

(untitled)
The main aim of this study is to investigate the influence of social capital of communities of practice on knowledge-sharing practices and innovation among Iranian knowledge-intensive industries; that is, financial and pharmaceutical industries. Numerous past studies centred on the resource-based theory of the firm, or the knowledge-based view of the firm, identified organizational factors that may serve as enablers or inhibitors to knowledge sharing and, subsequently, to organizational innovation. However these studies overlook the possible moderating role of social capital on the abovementioned relationship. This study attempts to address this gap and analyze the moderating role of social capital. The integrative model proposed here examines the moderating influence of social capital on the role of organizational factors such as information technology, innovation culture, organizational structure, reward system and management support on knowledge sharing and the innovation capability of a firm. A quantitative survey was conducted to collect data from 167 Iranian knowledge-intensive firms. This study then employed structural equation modeling to validate and confirm the integrative model using PLS-SEM software. Findings confirmed the direct impact of organizational enablers on knowledge sharing in different demographic variables such as age of the respondents and industry populations. The moderating role of social capital has been supported in two ways: first, the significant path coefficient (t-value) of its interaction with organizational structure and management support in financial firms and with shared language in the whole sample, and secondly, R2 significant changes of knowledge sharing and innovation capability with the presence of interaction effects in the whole population